Self-assembled polymeric nanocarrier-mediated co-delivery of metformin and doxorubicin for melanoma therapy - Mingming Song; Wentao Xia; Zixuan Tao; Bin Zhu; Wenxiang Zhang; Chang Liu; Siyu Chen (Taylor & Francis Group, 2021)
Malignant melanoma is a life-threatening form of skin cancer with a low response rate to single-agent chemotherapy. Although combined therapies of metformin (MET) and doxorubicin (DOX) are effective in treating a variety of cancers, including breast cancer, their different physicochemical properties and administration routines reduce the effective co-accumulation of both drugs in tumors. Nanoparticles (NPs) have been demonstrated to potentially improve drug delivery efficiency in cancer therapy of, for example, liver and lung cancers. Hence, in this study, we prepared pH-sensitive, biocompatible, tumor-targeting NPs based on the conjugation of biomaterials, including sodium alginate, cholesterol, and folic acid (FCA). As expected, since cholesterol and folic acid are two essentials, but insufficient, substrates for melanoma growth, we observed that the FCA NPs specifically and highly effectively accumulated in xenograft melanoma tumors. Taking advantage of the FCA NP system, we successfully co-delivered a combination of MET and DOX into melanoma tumors to trigger pyroptosis, apoptosis, and necroptosis (PANoptosis) of the melanoma cells, thus blocking melanoma progression. Combined, the establishment of such an FCA NP system provides a promising vector for effective drug delivery into melanoma and increases the possibility and efficiency of drug combinations for cancer treatment.